The Effect Of Random Word Game In Improving English Vocabulary - Evi Kartini Putri; Muhammad Hanafi; Sam Hermansyah; Nuraini K (La Ogi : English Language Journal, 2021)
The purpose of this study was determined whether the use of random word games could improved the ability of SMP N 2 Pancarijang students in vocabulary and whether students are interested in the method of this game. This study uses a mixed research method that was a quantitative research. The population of this study was seventh grade students of SMP N 2 Pancarijang in the 2018-2019 academic year. The total population was 87 students consisting of 4 classes. Class VII3 was taken as a sample using cluster sampling techniques, the total number of samples was 21. The instruments used in this study were vocabulary tests.The results of this study indicate that the pre-test got an average score (29,28) while the post-test got an average score (52,85). This shows that there was a significant difference between the pre-test and post-test. The p-value (0,00) is lower than the significant level (alpha (Î±) = 0,05). This means H1 was accepted. This study concluded that vocabulary teaching using the random word game improved students' ability to master vocabulary mastery in seventh grade students of SMP N 2 Pancarijang.